Optimized Deep Learning for Enhanced Trade-off in Differentially Private Learning - Geetha, P.; Naikodi, C.; Suresh, L. (Engineering, Technology & Applied Science Research, 2021)
Privacy and data analytics are two conflicting domains that have gained interest due to the advancements of technology in the big data era. Organizations in sectors such as finance, healthcare, and e-commerce take advantage of the data collected, to help them enable innovative decision making and analysis. What is sidelined is the fact that the collected data have associated private data of the individuals involved, and may be exploited and used for unjustified purposes. Defending privacy and performing useful analytics are two sides of the same coin, and hence achieving a good balance between these is a challenging scenario. This paper proposes an optimized differentially private deep learning mechanism that enhances the trade-off between the conflicting objectives of privacy, accuracy, and performance. The goal of this paper is to provide an optimal solution that gives a quantifiable trade-off between these contradictory objectives.